Real Exchange Rate Fluctuations and the Business Cycle : Evidence From Japan - Prasad, Eswar (IMF Working Papers; Working Paper, 1996)
This paper analyzes the relationship between the real exchange rate and the business cycle in Japan during the floating rate period. A structural vector autoregression is used to identify different types of macroeconomic shocks that determine fluctuations in aggregate output and the real exchange rate. Relative nominal and real demand shocks are found to be the main determinants of variation in real exchange rate changes, while relative output growth is driven primarily by supply shocks. Historical decompositions suggest that the sharp appreciations of the yen in 1993 and 1995 and its subsequent depreciation can be attributed primarily to relative nominal shocks.